Young Kidney-Transplant Recipient Woman with Recurrent Urinary Tract Infection and Graft Rejection: A Case Report - Nursamsu, Nursamsu; Febriliant, M. Reza (UI Scholars Hub, 2019)
Urinary tract infection (UTI), especially recurrent UTI, is a common problem, occurring in >75% of kidney transplant recipients. Urinary tract infection (UTI) can reduce the quality of life, graft potential, and patient survival. Urosepsis with impairment of graft function is potential long-term sequelae of recurrent UTI in kidney transplantation recipients. We present a case of UTI that developed within a month after renal transplant. The patient got a urinary tract infection repeatedly. We suspect lack of hygiene as the cause of urinary tract infection, the patient was rarely cleaning-up, took a bath, changing clothes, and did not wash after urinating. But, after we did some interventions, the patient still had urinary tract infection. Laboratory findings showed decreasing of renal function since one month before. Urine culture result showed that the cause of infection was Klebsiella pneumonia. Uroflowmetry result showed post void residual about 50-60 cc. We suspected anatomy anomaly at the urinary tract of this patient. To evaluate the renal graft without biopsy, we conducted an MRI and found a pyelonephritis renal graft. We got increasing CMV antibody for opportunistic infection. The last, renal biopsy result was acute cellular rejection. After giving appropriate treatment with ganciclovir 1 x 250 mg up to 6 months and cotrimoxazole 1 x 960 mg for 14 days, the renal function still decreased and so did the urine output, then the patient fell down into graft rejection.